Evaluasi Atas Implementasi Pernyataan Standar Akuntansi Pemerintahan Nomor 13 Pada BLUD Puskesmas Kawasan Terpencil - Wijoseno Lelono; Dodik Siswantoro (Jurnal Akademi Akuntansi, 2023)
Purpose: This study aims to evaluate the suitability of accounting and presentation of BLUD Puskesmas Financial Statements with the Statement of Government Accounting Standards Number 13, and identify the role of financial guidance carried out by the Health Office and the Regional Financial Management Officer (PPKD). Methodology/approach: This research was conducted at BLUD Puskesmas X, with a qualitative method through a case study approach. The data collection methods adopted in this study include document analysis and interviews Findings: The results showed that the condition of the presentation of the Financial Statements of BLUD Puskesmas X was not fully in accordance with PSAP 13, and the implementation of accounting was not fully in accordance with SE Director General of Bina Keuda No. 981/4092/KEUD, namely without making journals, posting to the General Ledger, and preparing the Balance Sheet. In terms of guidance, the Health Office has provided various coaching activities related to the preparation of Financial Statements, while PPKD               has not provided intensive guidance and is more directed at reconciling financial data between BPKAD and BLUD Puskesmas X. Practical and Theoretical contribution/Originality: This research is expected to provide suggestions and insights for BLUD Puskesmas management regarding aspects of the Financial Statement preparation process that require improvement, as well as contributing information for further research related to the development of Accounting, especially the implementation of Public Sector Accounting Standards Research Limitation: The interview process was conducted via online media and telephone due to geographical location considerations, namely BLUD Puskesmas X is located relatively far from the capital city of District AAA, about 295 KM with inland road access conditions on Borneo Island.